Interventions for Managing Picky Eating in Preschool Children: Literature Review - Endang Susilowati; Alfi Umayah; Anggie Diniayuningrum (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Picky eating in children is a widespread issue that can affect growth and development. Factors contributing to picky eating include parental influence, early feeding practices, and environmental conditions. Addressing picky eating behavior is crucial to prevent long-term negative effects on children's nutrition and health. Objective: This study aimed to evaluate the effectiveness of various interventions, such as sensory education, parent training, oral interventions, massage, and diet adjustments, in improving picky eating behavior in children. Method: A review of 15 studies published between 2013 and 2023 was conducted, focusing on intervention programs for children aged 1-6 years. The studies were selected from databases like PubMed, Science Direct, and Google Scholar. Result: Sensory education helped reduce food rejection by familiarizing children with new foods. Parent training, including cooking classes and the Baby Led Weaning (BLW) method, effectively reduced picky eating. Oral interventions, such as herbal remedies and appetite-enhancing supplements, showed positive outcomes. Massage techniques like Tui Na and tailored dietary plans also contributed to better eating habits in both underweight and overweight children. Conclusion: Interventions including sensory education, parental training, oral treatments, massage, and diet modifications can significantly improve eating behaviors in picky eater children, promoting healthier nutrition and growth.